Bacterial Isolates and Drug Susceptibility Pattern of Sterile Body Fluids from Tertiary Hospital, Northern Ethiopia: A Four-Year Retrospective Study. (21st May 2019) - Tsegay, Ephrem; Hailesilassie, Aregawi; Hailekiros, Haftamu; Niguse, Selam; Saravanan, Muthupandian; Abdulkader, Mahmud
Abstract : This study was conducted in Ayder comprehensive specialized Hospital, Mekelle, Northern Ethiopia, to determine the bacterial profiles and drug susceptibility pattern from body fluids. A total of 218 patients were investigated, of which 146 (67%) were males. The age of the study subjects ranged from 2 days to 80 years with 96(44%) in the age group of 15 years and above. The overall bacterial infection was 44 (20.2 %) of which gram positive bacteria were prevalent, 23 (52.3%) than gram negative bacteria 21 (47.7%). The predominantly isolated bacteria were S. pneumonia, followed by K.pneumoniae, S. aureus, and E coli. Multidrug resistance was observed in 12 (100%) of the isolated gram positive bacteria and in 6 (75%) of the isolated gram negative bacteria.